Analisis Sikap Moderasi Beragama Pada Kisah Nabi Ibrahim dalam Al-Quran - Febriyarni, Busra; Harmi, Hendra; Yusefri (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
This paper aims to describe the attitude of religious moderation of the prophet Ibrahim in the Qur'an. There are 9 suras that are used as the focus of the study, namely: Al-Baqarah 124, An-Nisa 125, Al-An'am 74 - 79, Ibrahim 35 - 41, Maryam 41 - 50, Al-Anbiya '55 - 67, Asy-Syuara' 83 - 87, Ash-Shaffat 99 - 102 and Shad 45 - 48. 87 from various tafsir books that have appeared in Indonesia, namely the book Tafsir Al-Mishbah by Muhammad Quraish Shihab, Al-Azhar's tafsir by Buya Hamka, the tafsir of the Ministry of Religious Affairs of the Republic of Indonesia and the tafsir of Hidayatul Insan Bi Tafsiril Qur'an by Marwan Hadidi bin Musa. Furthermore, to find out the value of religious moderation contained in the verses that tell the story of the prophet Ibrahim, researcher used library research, with an effort to dig up data in depth from various Indonesian tafsir books thematically. The results of the study show that the values ​​of religious moderation in the story of the Prophet Ibrahim are: a high national commitment to love his homeland, the value of tolerance, the value of monotheistic dialogue, the value of love for the homeland, anti-violence, persuasive communication and open dialogue (deliberation).